2020
DOI: 10.1002/cam4.3614
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of synchronous multiple primary lung cancer after surgical treatment: A systematic review and meta‐analysis of current evidence

Abstract: Background This study aims to quantitatively summary the characteristics of synchronous multiple primary lung cancer (sMPLC), postoperative mortality, long‐term prognosis, and prognostic effects of potential clinical parameters in patients with sMPLC after surgery. Methods PubMed and Embase databases were systematically searched to identify studies that explored the prognosis of patients with sMPLC after surgery. Results Fifty‐two studies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Adenocarcinoma accounts for the largest portion, among which acinar, lepidic, and papillary adenocarcinomas are the three most frequent architectural patterns. 10 , 11 In 1975, Martini and Melamed proposed the first clinicopathological diagnostic criteria for MPLC. 3 This standard has been widely accepted by clinicians and pathologists, and has been an important diagnostic reference for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma accounts for the largest portion, among which acinar, lepidic, and papillary adenocarcinomas are the three most frequent architectural patterns. 10 , 11 In 1975, Martini and Melamed proposed the first clinicopathological diagnostic criteria for MPLC. 3 This standard has been widely accepted by clinicians and pathologists, and has been an important diagnostic reference for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous MPLC (sMPLC) was first discovered by Beyreuther in 1924. 10 Despite its rarity, the incidence of sMPLC has been increasing. 11 , 12 Smoking, lymph node metastasis, and pleural invasion are independent risk factors regarding the prognosis of patients with sMPLC, while early detection and operation can improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with MPLC are diagnosed with multiple ground glass opacities (GGOs) simultaneously, and therefore, surgery is the mainstay of management in the early stages of the disease [ 10 , 11 ]. The proportion of patients with sMPLC and 5-year survival rate is increasing, whereas the postoperative mortality is decreasing [ 12 ]. A previous meta-analysis revealed that age, sex, pulmonary function, smoking, tumor size, surgical methods, and lymph node status are prognostic factors for sMPLC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients with sMPLC and 5-year survival rate is increasing, whereas the postoperative mortality is decreasing [ 12 ]. A previous meta-analysis revealed that age, sex, pulmonary function, smoking, tumor size, surgical methods, and lymph node status are prognostic factors for sMPLC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%